2018
DOI: 10.1016/j.ijdrr.2018.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Ebola crisis response in the USA: Communication management and SOPs

Abstract: A B S T R A C TThis research focuses on the 2014 Ebola crisis response by emergency managers in the Dallas-Fort Worth (DFW) Metropolitan region in the State of Texas, U.S.A. It examines the patterns of crisis communication and the use of Standard Operating Procedures (SOPs) during the first month of the crisis. Primary data collected from 24 faceto-face interviews and 12 online surveys are analyzed. The research identifies elements contributing to organizational failures, which by their very nature gain public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Due to the virus' dissemination across geographical boundaries and sectors, there is no clear direction about who owns the crisis (Andrew et al, 2018). This requires stakeholder management and getting in touch and fine-tuning tasks and competencies across fields, including governmental parties, general practitioners (Andrew et al, 2018), media (Chen, 2008;McMonagle, 2020;Park, Boatwright, & Avery, 2019;Rossmann, Meyer, & Schulz, 2018;Saxon, Bass, Wright, & Panick, 2019), laboratories and hospitals (Dickmann, Biedenkopf, Keeping, Eickmann, & Becker, 2014) and healthcare workers. From the SARS outbreak, we know that communicating with domestic and international policymakers, financial markets, travel industry, and other key sectors is relevant as well (Smith, 2006).…”
Section: Domain Iv: Interaction With Stakeholdersmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the virus' dissemination across geographical boundaries and sectors, there is no clear direction about who owns the crisis (Andrew et al, 2018). This requires stakeholder management and getting in touch and fine-tuning tasks and competencies across fields, including governmental parties, general practitioners (Andrew et al, 2018), media (Chen, 2008;McMonagle, 2020;Park, Boatwright, & Avery, 2019;Rossmann, Meyer, & Schulz, 2018;Saxon, Bass, Wright, & Panick, 2019), laboratories and hospitals (Dickmann, Biedenkopf, Keeping, Eickmann, & Becker, 2014) and healthcare workers. From the SARS outbreak, we know that communicating with domestic and international policymakers, financial markets, travel industry, and other key sectors is relevant as well (Smith, 2006).…”
Section: Domain Iv: Interaction With Stakeholdersmentioning
confidence: 99%
“…In their analysis of a case of Ebola in Texas, Andrew and colleagues (2018) describe how some agencies perceived the US Centers for Disease Control and Prevention's (CDC) response as slow and inadequate, while other agencies reported that the CDC did the best they could under the circumstances and were able to distribute guidance documents in a timely manner. We should resist the tendency to assess only the things that went wrong, as there is a need to ensure that as a crisis unfolds, successes are noted and praised as well (Andrew et al, 2018). Many outcomes of crisis management will lie somewhere in-between "failure" and "success," given that the real world is often messy (McConnell, 2011).…”
mentioning
confidence: 99%
“…Coordination requires task interdependencies and mechanisms such as partner-specific communications, rules and procedures, routines, liaison, integration of roles, and interim authorities (Hartgerink et al, 2014), which foster interorganizational coordination (Kozuch & Sienkiewicz-Małyjurek, 2016). Coordination is often required when legally independent entities such as local governments in an MSA need to work in concert to address complex and wicked problems such as a health crisis (Andrew et al, 2018; K. Kim et al, 2017).…”
Section: Coordination Effectiveness During Public Health Emergenciesmentioning
confidence: 99%
“…The political autonomy of governments often leads to confusion about who owns a public health emergency and who should oversee the response effort (Andrew et al, 2018; K. Kim et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation